Caribbean Report 28-05-1999 - The British Broadcasting Corporation; Greaves, Keith Stone (anchor, correspondent); Fletcher, Pascal (correspondent); Norton, Michael (correspondent); Shillingford, Henry (interviewee); Smith, Lew (correspondent); Greste, Peter (correspondent); Richardson, Wakefield (correspondent); Becca, Tony (interviewee) (The British Broadcasting Corporation, 1999)
1. Headlines with anchor Keith Stone Greaves (00:27) 2. Cuban President Fidel Castro has removed his foreign minister Roberto Robaina from his cabinet. Havana based journalist Pascal Fletcher reviews the new appointment (00:28 - 03:06) 3. In Haiti, the private sector and trade union associations are holding peaceful rallies in response to a spate of brutal murders and shootings in parts of the country. Michael Norton reports on the significance of the rallies (03:07 - 05:31 4. During the last day of the Meeting of the International Whaling Commission in Grenada, officials approve a request by Saint Vincent and the Grenadines to allow its whaling operations for the next three years. US, New Zealand, Mexico and Australia voice reservations. Commission Programme Director of the Dominica Conservation Association Henry Shillingford discusses the precedence set by the ruling. Lew Smith reports (05:32 – 08:35) 5. Cooperation in response to natural disasters in the region and focus on global economic problems are two agenda issues addressed at the Latin American Summit in Mexico. BBC correspondent Peter Greste reports (08:36 - 10:30) 6. At a conference in Sweden the international community pledged nine million dollars worth of aid for five Central American countries affected by Hurricane Mitch last year. The InterAmerican Development Bank and the World Bank will provide half of the aid money (10:31 – 10:54) 7. One week after the resignation of Anguilla Finance Minister Victor Banks the political climate remains tense. Wakefield Richardson reviews the ongoing political impasse (10:55 - 12:47) 8. The US marines admitted that one of its jet fired two hundred and sixty radioactive shells in Puerto Rico. Puerto Ricans are calling on US armed forces to withdraw from the country (12:48 - 13:32) 9. Within the Caribbean there is favorable response to the appointment of Vivian Richards as coach of the West Indies team for the current World Cup. He replaces Malcolm Marshall. Sports journalist Tony Becca discusses ...